Actual Status of Public Policy Studies in Libya - Imneina, Dr.Abeir (Dirasat in Economics and Business, 2009)
The study aimed (0 intro duce and identify the reality and importance of the Libyan studies of the Public Policy by exploring the Academic out put. Therefore, the following ind ications were dealt with: a) Teaching the subject of Pub lic Policy and to be considered part of the curriculurns taught in Political science collages wit hin the universities of Libya. b) Holding conferences and ro undtables on Public Policy.